Strategic Management of the Regional Inspectorate as an Effort to Improve Transparent and Accountable Education Governance - dedi candira; Hamengkubuwono; Jumira Warlizasusi; Irwan Fathurrochman (International Journal of Education Research and Development, 2025)
This study aims to analyse the implementation of strategic management in the Strategic Plan (Renstra) of the Kepahiang Regency Inspectorate and its contribution to improving more transparent and accountable education governance. The research approach used is descriptive qualitative with a case study method, which focuses on document analysis, observation, and relevant documentation. The research stages include preliminary studies, data collection, data analysis using the SWOT model, and conclusion drawing. The results of the study indicate that the Renstra of the Inspectorate has adopted strategic principles well, including vision, mission, strategic objectives, and performance indicators that support the strengthening of the Inspectorate's role in supervising the education sector. Strengths such as the integrity of human resources, a well-planned supervisory structure, and central policy support are important institutional assets. However, there are still weaknesses in terms of the limited number of auditors, follow-up on supervisory results, and the use of information technology. External opportunities, such as the push for bureaucratic reform and strengthening inter-institutional synergy, need to be leveraged to address threats such as low commitment from education-related government agencies. The discussion indicates that the success of oversight depends heavily on the consistent implementation of strategic management and the internalization of values such as trustworthiness, accountability, and integrity, as emphasized in the perspective of Islamic Education Management.